1983
DOI: 10.3109/17453678308996613
|View full text |Cite
|
Sign up to set email alerts
|

Indium-111 Leucocyte Scanning in the Evaluation of Painful Hip Arthroplasty

Abstract: Thirty patients with a painful hip arthroplasty had an In-111 leucocyte scan before surgical reexploration. In 12 patients, the In-111 leucocyte scan was abnormal and in all of them, microorganisms were found at the culture of the material from their hips at the operation. Among the 18 patients with a normal scan no infection was found in 17. In one patient, a thick-walled abscess growing Escherichia coli was found. We conclude that In-111 scanning is sensitive, specific and therefore useful in the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Scintigraphic examination with Tc-99 MDP has been commonly recognized as having a low specificity [3,4,9] in diagnosing infection, owing to unspecific increased uptake in noninfected arthroplasties more than 6 months after surgery. Scintigraphy with 111-indium oxine-labelled cells and with Tc-99 HmPAC white blood cells seemed to be good diagnostic tests [12,15,17,21,25,26], although other authors have reported a limited role for them in the detection of infection in a THA [14,29]. Joint aspiration is not exempt from problems, such as pain and risk of infection [2,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Scintigraphic examination with Tc-99 MDP has been commonly recognized as having a low specificity [3,4,9] in diagnosing infection, owing to unspecific increased uptake in noninfected arthroplasties more than 6 months after surgery. Scintigraphy with 111-indium oxine-labelled cells and with Tc-99 HmPAC white blood cells seemed to be good diagnostic tests [12,15,17,21,25,26], although other authors have reported a limited role for them in the detection of infection in a THA [14,29]. Joint aspiration is not exempt from problems, such as pain and risk of infection [2,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest studies with 30 patients examining labeled leukocytes with bone marrow imaging and hip arthroplasty by Mulamba et al [28] observed a 92% sensitivity and 100% specificity for diagnosing hip infections. Another study of LS/BMS in 72 patients with hip arthroplasty demonstrated 100% sensitivity and 97% specificity in diagnosing infection [15].…”
Section: Discussionmentioning
confidence: 99%
“…4) . The overall accuracy of combined leukocyte/marrow imaging is approximately 90% (Mulamba et al, 1983;King et al, 1990;Seabold et al, 1991;Achong et al, 1994;Palestro et al, 1998;Joseph et al, 2004;.…”
Section: In-vitro Labeled Leukocytesmentioning
confidence: 99%
“…Radionuclide imaging, which reflects physiologic rather than anatomic changes, and is not affected by metallic hardware, plays an important role in the evaluation of prosthetic joint infection. The current imaging procedure of choice for evaluating suspected joint replacement infection is combined leukocyte/marrow imaging with an overall accuracy ranging from 88%-98% (Mulamba et al, 1983;Joseph et al, 2001;. Although inflammation may be present in both the infected and aseptically loosened device, neutrophils, which are invariably present in infection, are usually absent in aseptic loosening.…”
Section: Prosthetic Joint Infectionmentioning
confidence: 99%